Perceptions of pregnant women about obstetric violence (Research, Society and Development, 2025)
Obstetric violence refers to any form of disrespectful, abusive or non-consensual treatment that a woman may suffer during prenatal, childbirth and postpartum care by health professionals. This study aims to understand the perception of pregnant women about obstetric violence. This is a descriptive research with a qualitative approach carried out in the city of Guanambi-BA. It was conducted in Basic Health Units that serve pregnant women from the urban and rural perimeter, in central and peripheral neighborhoods. A total of 23 interviews were conducted, which were defined based on the data saturation criterion. The data collection instrument used was a semi-structured interview script. Data analysis was performed using Bardin's Content Analysis. This study complies with Resolution 466/2012 of the National Health Council in all its stages. The results obtained showed a significant discrepancy in the level of knowledge about the concept of obstetric violence when comparing pregnant women living in rural areas and peripheral neighborhoods with those living in central neighborhoods. It also showed that many pregnant women have limited perception of the concept of obstetric violence, understanding that it occurs mostly at the time of delivery. The conclusion is that there is a need to increase awareness among pregnant women about their rights, to raise awareness among health professionals about the topic and contraindicated practices, to involve society and to strengthen health education strategies that promote a more comprehensive understanding of obstetric violence.